STUDY OF MACHINING OF THERMAL RECTIFICATED Corymbia citriodora AND Pinus elliottii - Bilesky, Luciano Rossi; Sampaio Alves, Manoel Cleber de [UNESP]; Antunes Vieira, Fabio Henrique; Deus, Priscila Roel de (Univ Federal Vicosa, 2018)
This study evaluated the influence of thermal rectification in machining Corymbia citriodora and Pinus elliottii. The heat treatment was carried out for 6 hours at temperatures of 100 degrees C, 140 degrees C, 160 degrees C, 180 degrees C and 200 degrees C and evaluated the performance of machining in three different material cutting tools, polished and hard metal carbide with TiB2 coating. The cutting power and roughness R-a and R-t of the machined surfaces with three different tools were evaluated. The power has proven lower for Pinus elliottii species. The roughness was lower for Corymbia citriodora wood. The roughness R-a and R-t were lower for heat treatment temperature of 180 degrees C.
Keywords: Heat treatment; Cylindrical turning; Roughness